2015
DOI: 10.1093/ajh/hpv095
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Resting Heart Rate and Incident Hypertension: The Henry Ford Hospital Exercise Testing (FIT) Project

Abstract: Elevated RHR is an independent risk factor for incident hypertension, particularly in younger persons. Whether lifestyle modification or other strategies to reduce RHR can prevent incident hypertension in high-risk individuals warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 28 publications
3
38
0
1
Order By: Relevance
“…Previous studies regarding whether age modified the association between RHR and cardiovascular events or risk factors generated inconsistent results. For example, two previous studies reported that the associations between faster RHR and risk of hypertension 27 and diabetes 28 were stronger in participants with younger age. In contrast, in another study regarding total and cardiovascular disease mortality, the interaction between age and RHR was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies regarding whether age modified the association between RHR and cardiovascular events or risk factors generated inconsistent results. For example, two previous studies reported that the associations between faster RHR and risk of hypertension 27 and diabetes 28 were stronger in participants with younger age. In contrast, in another study regarding total and cardiovascular disease mortality, the interaction between age and RHR was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate is regulated by complex interactions of biological systems, including the autonomous nervous and hormonal systems 12 . In addition, resting heart rate is associated with many other cardiovascular risk factors, including blood pressure, smoking, glucose metabolism, lipids, C-reactive protein, metabolic syndrome, body mass index, and diabetes mellitus [13][14][15][16] . In some conditions, including heart failure, reduction of heart rate has been directly demonstrated to lead to event reduction providing evidence that heart rate is indeed a modifiable causal risk factor and not just a risk marker or a reflection of comorbidities 11 .…”
mentioning
confidence: 99%
“…Elevated resting heart rate has been associated with development of risk factors including diabetes 9 and hypertension 10 . It has previously been suggested that the association between resting heart rate and heart failure is driven by accelerated coronary atherosclerosis via increased inflammation, endothelial dysfunction, and ventricular remodelling due to increased metabolic stress 11 .…”
Section: Discussionmentioning
confidence: 99%